1998
DOI: 10.1177/14034948980260020201
|View full text |Cite
|
Sign up to set email alerts
|

How to measure sickness absence? Literature review and suggestion of five basic measures

Abstract: We have reviewed sick-leave measures previously used in the literature and suggested five basic measures for assessing sick-leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(176 citation statements)
references
References 23 publications
3
167
0
6
Order By: Relevance
“…Hensing et al [29] have provided five basic SA measures for research on the population level. However, international agreement on SA measures on the individual level, for example on the definitions of shortterm and long-term SA, is lacking.…”
Section: Rtw Rates In Different Categories Of Mental Disordersmentioning
confidence: 99%
“…Hensing et al [29] have provided five basic SA measures for research on the population level. However, international agreement on SA measures on the individual level, for example on the definitions of shortterm and long-term SA, is lacking.…”
Section: Rtw Rates In Different Categories Of Mental Disordersmentioning
confidence: 99%
“…the population at work and not the general population, etc. As Hensing et al strongly recommend, the research field would gain from better standardization in the measures used [41], and the contributions of this Scandinavian research group are seminal.…”
Section: Sickness Absencementioning
confidence: 99%
“…(3) Recommended measures. Hensing et al [41] recommended five measures for sick leave that have become a bit of a reference standard in clinical and epidemiological literature on spinal disorders. Not all measures make sense in every outcome study; however, they make more sense in studies that include follow-ups and a control group, or representative reference dates of the population under study.…”
Section: Measurement Problems and Recommendationsmentioning
confidence: 99%
“…Some studies reported on SA as a dichotomous (yes/no) outcome (Kouzis and Eaton 1994;Laitinen-Krispijn and Bijl 2000;Bültmann et al 2005;Eriksen et al 2003;Ahola et al 2008;Krantz and Ostergren 2002), others reported on the frequency of SA spells (Kivimäki et al 2001(Kivimäki et al , 2007Väänänen et al 2003;Duijts et al 2006) or the total number of SA days (Kessler and Frank 1997;Dewa and Lin 2000;Suija et al 2009;Kruijshaar et al 2003;Broadhead et al 1990;Andrea et al 2003;Ahola et al 2008). Few studies analyzed SA both in terms of frequency and duration as recommended by Hensing et al (1998). SA was either established by self-report (Hilton et al 2008;Kessler and Frank 1997;Dewa and Lin 2000;Kouzis and Eaton 1994;Suija et al 2009;Kruijshaar et al 2003;Broadhead et al 1990;Jenkins 1985;Laitinen-Krispijn and Bijl 2000;Eriksen et al 2003;Borritz et al 2006) or by organizational absence records (Bültmann et al 2005(Bültmann et al , 2006Virtanen et al 2007;Kivimäki et al 2001Kivimäki et al , 2007Bourbonnais and Mondor 2001;Andrea et al 2003;Väänänen et al 2003;Lexis et al 2009;Duijts et al 2006;…”
mentioning
confidence: 99%